The Optimal Cesarean Skin Incision in Patients with Super Obesity - Seif, Karl E.; Goetzinger, Katherine R.; Turan, Ozhan M. (American Journal of Perinatology, 2022)
Objective This study aimed to evaluate if supraumbilical midline vertical incision performed in patients with a hanging pannus (umbilicus at the level of the pubic bone) is a reasonable alternative to the Pfannenstiel in patients with body mass index (BMI) ≥ 50 kg/m2 undergoing cesarean delivery.Study Design Retrospective cohort study in patients with BMI ≥ 50 kg/m2 undergoing cesarean delivery at a single center from 2016 to 2020. Study groups were Pfannenstiel's versus supraumbilical vertical skin incision. If patients had a hanging pannus (umbilicus at the level of the pubic bone), vertical incisions were performed. Otherwise, Pfannenstiel's incision was performed. Decision for the incision was made prospectively. Primary outcome was a composite of need for blood transfusion, presence of immediate surgical complications, and presence of delayed surgical complications. Secondary outcomes included the individual components of the primary outcome, the median surgical blood loss, total operative time, time from skin incision to delivery of neonate, hysterotomy type, and neonatal outcomes. MedCalc 19.5.1 was used for analysis.Results A total of 103 patients with BMI ≥50 kg/m2 were included. Of those, 68 (66%) had Pfannenstiel's and 35 (34%) had supraumbilical vertical incisions. There was no statistically significant difference in the incidence of the primary outcome (12 vs. 11%, p = 0.96). There was neither significant difference in immediate or delayed postoperative complications nor in neonatal outcomes. However, patients in the vertical midline incision group were more likely to have a classical hysterotomy (52%) compared with the Pfannenstiel group (6%; p < 0.05), increased overall median surgical blood loss (1,000 vs. 835 mL, p < 0.05), and increased total surgical time by a median of 30 minutes (p < 0.05).Conclusion In patients with super obesity and hanging pannus, performing a supraumbilical vertical midline incision offers a reasonable alternative to Pfannenstiel's incision, but patients should be counseled about the increased risk for classical hysterotomy and implications in future pregnancies.Key Points
Keywords: abdominal incision; cesarean section; complications; pannus; Pfannenstiel's incision; postoperative morbidity; pregnancy; super obesity; supraumbilical vertical incision